2021
DOI: 10.3389/fnins.2021.651574
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Unit-Based Personalized Fingerprint Feature Selection Strategy for Dynamic Functional Connectivity Networks

Abstract: The sliding-window-based dynamic functional connectivity networks (SW-D-FCN) derive from resting-state functional Magnetic Resonance Imaging has become an increasingly useful tool in the diagnosis of various neurodegenerative diseases. However, it is still challenging to learn how to extract and select the most discriminative features from SW-D-FCN. Conventionally, existing methods opt to select a single discriminative feature set or concatenate a few more from the SW-D-FCN. However, such reductionist strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In fact, similar high-order network methods have been applied in the field of functional magnetic resonance imaging (fMRI) (Zhao et al, 2018(Zhao et al, , 2021Zhou et al, 2018), where experimental results have shown that the high-order network method can explore more advanced features on the basis of the traditional low-order network. However, owing to the low temporal resolution of fMRI, the Gaussian distribution leads to inaccurate estimation results.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, similar high-order network methods have been applied in the field of functional magnetic resonance imaging (fMRI) (Zhao et al, 2018(Zhao et al, , 2021Zhou et al, 2018), where experimental results have shown that the high-order network method can explore more advanced features on the basis of the traditional low-order network. However, owing to the low temporal resolution of fMRI, the Gaussian distribution leads to inaccurate estimation results.…”
Section: Introductionmentioning
confidence: 99%
“…FC network has been of great importance for discovering the functional organization of human brain and searching for the biomarkers of the neuropsychiatric disorders, such as Alzheimer’s disease ( Chen et al, 2017 ; Hao et al, 2017 ) and autism spectrum disorder (ASD) ( Zhao et al, 2018 ; Wee, Yap & Shen, 2016 ). Currently, researchers have proposed various FC network modeling methods for ASD assisted diagnosis ( Liu & Huang, 2020 ; Zhao et al, 2020 ; Zhao et al, 2021 ). For example, Liu & Huang (2020) estimated the severity of ASD by multivariate model analysis, and they found that some FCs suffer from abnormal alterations in ASD patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu & Huang (2020) estimated the severity of ASD by multivariate model analysis, and they found that some FCs suffer from abnormal alterations in ASD patients. Zhao et al (2021) proposed a unit-based personalized fingerprint feature selection (UPFFS) strategy and applied to ASD, they found that the top selected discriminative brain regions by UPFFS are related to visual processing, social cognition, and emotional expression which is associated with ASD. Overall, previous studies have shown that FC networks have great potential for revealing FC deficits and finding abnormal brain regions in ASD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation